Exploitation and evaluation of the tilapia fishery (Oreochromis spp.) in the Fernando Hiriart Balderrama “Zimapám” Reservoir, Hidalgo, Mexico - Gómez-Ponce, Mario A. (2012)
Oreochromis spp. fishing in the Fernando Hiriart Balderrama Reservior began in 1997 and its effects had never been studied before. Schaefer and Fox’s biomass dynamic model were used in order to obtain the first evaluation of this resource and to analyze the presence of record errors (or observation errors) in the annual total catch data set. The number of fishermen was used as the fishing effort unit. Schaefer´s model proved to be statically reliable: Oreochromis spp. was estimated at the maximum population size value of k = 9 000 tons and reproduction rate value at annual r = 0.730. Considering those ecological and biological strategies, Schaefer´s model showed that great biomass levels (predicted biomass) have been produced in the Zimapán reservior; however, only a small part of this biomass was exploited during the analyzed period. The results indicate that tilapia fishery in the Zimapán Reservoir was at equilibrium or was not over-fished between 1997 and 2006 because historical tilapia records observed in Schaefer´s model were far from the k parameter and below the MSY value. With this exploitation type, the fishing effort can increase to up to 7 203 fishermen (level of fishing effort at which the maximum sustainable yield is achieved (fMSY)). However, in order to avoid an increase of the non-controlled fishing effort a similar analysis is recommended with recent data.